2019
DOI: 10.1007/s12671-018-1087-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) in Real-World Healthcare Services

Abstract: Depression is common with a high risk of relapse/recurrence. There is evidence from multiple randomised controlled trials (RCTs) demonstrating the efficacy of mindfulness-based cognitive therapy (MBCT) for the prevention of depressive relapse/ recurrence, and it is included in several national clinical guidelines for this purpose. However, little is known about whether MBCT is being delivered safely and effectively in real-world healthcare settings. In the present study, five mental health services from a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 56 publications
10
46
1
1
Order By: Relevance
“…To compare this finding in further detail to previous RCTs, we collected within-group effect sizes of the change in BDI-II scores in the MBCT arms of relevant previous RCTs. 5 , 31 With regard to history of MDD, Tickell et al 30 demonstrated a moderate within-group effect (Cohen's d = 0.31) in patients with remitted, recurrent MDD with three or more episodes, whereas the effect size for remitted, recurrent MDD in our study was Cohen's d = 0.84. With regard to remission status of MDD, a study of patients with chronic MDD 28 found a moderate effect as well (Cohen's d = 0.48; our sample: current/recurrent Cohen's d = 0.76, current/single Cohen's d = 0.83), Van Aalderen et al 29 found moderate effects in both acute and remitted patients with MDD who suffered three or more previous episodes (Cohen's d = 0.71 and 0.45, respectively).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…To compare this finding in further detail to previous RCTs, we collected within-group effect sizes of the change in BDI-II scores in the MBCT arms of relevant previous RCTs. 5 , 31 With regard to history of MDD, Tickell et al 30 demonstrated a moderate within-group effect (Cohen's d = 0.31) in patients with remitted, recurrent MDD with three or more episodes, whereas the effect size for remitted, recurrent MDD in our study was Cohen's d = 0.84. With regard to remission status of MDD, a study of patients with chronic MDD 28 found a moderate effect as well (Cohen's d = 0.48; our sample: current/recurrent Cohen's d = 0.76, current/single Cohen's d = 0.83), Van Aalderen et al 29 found moderate effects in both acute and remitted patients with MDD who suffered three or more previous episodes (Cohen's d = 0.71 and 0.45, respectively).…”
Section: Discussioncontrasting
confidence: 71%
“…To compare this finding in further detail to previous RCTs, we collected within-group effect sizes of the change in BDI-II scores in the MBCT arms of relevant previous RCTs. 5,31 With regard to history of MDD, Tickell et al 30 That MBCT has comparable effects in patients with recurrent and single episodes of MDD in terms of depressive symptom reduction is in line with previous evidence suggesting that reduction of residual symptoms by MBCT is independent of number of previous episodes of MDD. 13 In terms of remission status, our results are also in accordance with evidence from a recent meta-analysis 5 indicating that MBCT was effective in the treatment of current depressive symptoms.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…While this supported implementation, its effects on effectiveness are unknown. A recent pragmatic study of MBCT’s effectiveness in NHS services sampled from some of our case study sites suggested that MBCT’s acceptability and outcomes were comparable when benchmarked against outcomes in randomised trials 34. Implementation literature35 36 suggests a dynamic interplay between an intervention, its implementation and context.…”
Section: Discussionmentioning
confidence: 91%
“…The first two papers address the question of the effectiveness of MBCT in naturalistic real-world settings. Tickell et al (2019) investigated the effectiveness of MBCT in five mental health services in different regions in the UK. In a sample of 1554 service users, they examined the effect of MBCT on depressive outcomes.…”
mentioning
confidence: 99%